2012
DOI: 10.1155/2012/150842
|View full text |Cite
|
Sign up to set email alerts
|

Morphine and Clonidine Synergize to Ameliorate Low Back Pain in Mice

Abstract: Chronic low back pain (LBP) is a debilitating condition associated with signs of axial and radiating pain. In humans with chronic LBP, opioids are often prescribed with varying outcomes and a multitude of side effects. Combination therapies, in which multiple pharmacological agents synergize to ameliorate pain without similar potentiation of adverse reactions, may be useful in improving therapeutic outcome in these patients. The SPARC-null mouse model of low back pain due to disc degeneration was used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 57 publications
1
19
0
2
Order By: Relevance
“…If similar synergistic interactions also occur in undesired side effects, then the therapeutic benefits will be limited. While few preclinical studies have directly addressed this question (Tajerian et al ., ), clinical studies have indicated that side effects remain generally unchanged with drug combinations that enhance analgesia or decrease overall opioid requirement (Förster and Rosenberg, ; Paech et al ., ). Additional studies are necessary to fully characterize the impact of opioid–adrenoceptor agonist co‐administration on analgesia versus undesired side effects.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…If similar synergistic interactions also occur in undesired side effects, then the therapeutic benefits will be limited. While few preclinical studies have directly addressed this question (Tajerian et al ., ), clinical studies have indicated that side effects remain generally unchanged with drug combinations that enhance analgesia or decrease overall opioid requirement (Förster and Rosenberg, ; Paech et al ., ). Additional studies are necessary to fully characterize the impact of opioid–adrenoceptor agonist co‐administration on analgesia versus undesired side effects.…”
Section: Discussionmentioning
confidence: 97%
“…For example, despite an extensive co‐expression of MOP receptors and α 2 ‐adrenoceptors in locus coerulus neurons, electrophysiological recordings revealed only an additive interaction among these receptors (Stone and Wilcox, ). Although synergistic interactions are observed when drugs are administered systemically (Ossipov et al ., ; Tajerian et al ., ), there is little evidence suggesting that synergy occurs outside the spinal cord. Further studies are therefore necessary to explore the full potential of other routes of administration that are more practical than spinal delivery for the treatment of chronic pain.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…19 Aynı nöron üzerinde yerleşmiş α-2 adrenerjik ve opioid reseptörleri arasında bir kooperasyon mevcut olabilir, veya birbirinden bağımsız olarak G protein aktivasyonları ile intrasellüler mekanizmaları değiştirerek aditif veya sinerjistik etki gös-teriyor olabilirler. 20 Bununla beraber, α-2 adrenerjik reseptörler opioid sistemden bağımsız etki gösteriyor olabilir, çünkü α-2 adrenerjik agonistlerin antinosiseptif etkisi, opioid antagonisti olan naloksan varlığından etkilenmemektedir. 20 Yapılan çalışmalarda, gönüllülere ven içi olarak verilen deksmedetomidinin postoperatif analjezide ağrı ve opioid tüketimini azalttığı belirlenmiştir.…”
Section: Grup D Grup P Punclassified
“…20 Bununla beraber, α-2 adrenerjik reseptörler opioid sistemden bağımsız etki gösteriyor olabilir, çünkü α-2 adrenerjik agonistlerin antinosiseptif etkisi, opioid antagonisti olan naloksan varlığından etkilenmemektedir. 20 Yapılan çalışmalarda, gönüllülere ven içi olarak verilen deksmedetomidinin postoperatif analjezide ağrı ve opioid tüketimini azalttığı belirlenmiştir. 13,21,22 Bizim çalışmamızda deksmedetomidin propofol ile karşılaştırıldığında, siyatik femoral sinir bloğunun postoperatif analjezik özellikleri üzerine istatistiksel olarak anlamlı etkileri olmamıştır.…”
Section: Grup D Grup P Punclassified